Analisis Faktor – Faktor Yang Mempengaruhi Price Earning Ratio pada Perusahaan Manufaktur yang Listing di BEI - Sari, Oktavia Komala; Handajani, Lilik; Pituringsih, Endar (E-Jurnal Akuntansi; Vol 30 No 12 (2020)DO - 10.24843/EJA.2020.v30.i12.p18, 2020)
This study aims to analyze what factors can affect the Price Earning Ratio (PER). Several factors that are considered to be able to influence PER which is used as a variable in this study, namely Return On Asset (ROA), Debt To Equity Ratio (DER), Dividend Pay Out Ratio (DPR), and Profit Growth Rate. . The population used is manufacturing companies listed on the IDX for the 2016-2018 period. With the purposive sampling technique, obtained 13 companies that will be used as research samples. The data used are secondary data. To see the effect of the independent variable on the dependent variable, multiple linear regression analysis tests were carried out which previously carried out the classical assumption test. Based on the results of the study, it is known that partially the results show that ROA, DPR, and Profit Growth Rate respectively have a significant effect on PER while DER has no significant effect on PER. Keywords: PER; ROA; DER; DPR; Profit Growth Rate.